Komposisi, Kekayaan, dan Kelimpahan Plankton di Perairan Sungai Simpang Heran dan Sungai Sugihan sebagai Instrumen Bioindikator Lingkungan Hidup - A. Setiawan A. Setiawan; R. Mohadi R. Mohadi; D. Setiawan D. Setiawan (Faculty of Mathtmatics and Natural Sciences, 2018)
The Simpang Heran dand Sugihan rivers has been planned for outlet factory by the OKI Pulp and Paper. The changing function of these areas give some effects to quality of water and biota around the river. The aims of this research is to study of plankton structure community as biomonitoring instrument. The re-search was conducted during August 2017. The location sampling was determined by purpossive random sampling method in 3 stations. The sampling in the moody area was carried out by Eckman grab. The results showed that 70 genera have been classified into 9 classes. Plankton abundance ranges from 372 - 408 ind/l highest found in the confluence of Sungai Simpang Heran and Sungai Sugihan. The species diversity index ranges from 3 - 3.08 and, the low dominant index is around 0.03.